Sustainable Ecology: Problems and the Perspective of Ecosystems in Tangkahan - Yayuk Yuliana; Endang Sulistya Rini; Sirojuzilam; Syafrizal Helmi Situmorang (Yayasan Ilomata, 2023)
Tourism is a priority sector. Ecotourism involves the community as one of the main actors and prioritizes resource sustainability. Ecological tourism is a sub-category of sustainable tourism or one of the market segments of natural environment-based tourism. The issue of sustainable development has become an important issue that needs to be disseminated in the midst of society and our country can compete and develop following the era of globalization. Ecotourism provides environmental, cultural and economic benefits to local communities. This article describes the management of sustainable ecotourism destinations for a region in Indonesia. Qualitative method is a descriptive method used in this study to provide an overview of the object under study. The results of the study show that the development of ecotourism in Tangkahan is through ecotourism stakeholders who are involved in ecotourism development which in turn has an impact on ecotourism development. Pandemic- era tourism must be able to be developed properly so that health protocols are still carried out but can still attract visitors. Prepare plans that are in accordance with human needs for tourism but are still aligned with protocols for the health of visitors, managers and the community.